Motiv ribe faronike v slovenski književnosti in likovni umetnosti 20. stoletja - Tucovič, Vladka (Traditiones (Ljubljana), 2006)
The article analyses intertextual and intermedial relation between a motif of a pregnant fish calld Faronika, from a Slovene folk song from the settlement of Podmelec in Baška grapa, and its transfer to literature and fine arts of the 20th century. The transformation in a weak text train is observed in proseworks Plebanus Joannes by Ivan Pregelj, Na rožnatem hrbtu faronike by Saša Vuga, Riba Faronika by Gustav Strniša and in intremedial relation in art works by Marij Pregelj, France Mihelič, Marko Pogačnik and Boštjan Kavčič.
Keywords: ethnology; etnologija; slovenska mitologija; slovenska folkloristika; slovensko ljudsko slovstvo; slovenska likovna umetnost